2016
DOI: 10.21873/anticanres.11058
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Solid and Micropapillary Components in Invasive Lung Adenocarcinomas Measuring ≤3 cm

Abstract: S+ and/or MP+ status predict worse prognosis in patients with acinar- and papillary-predominant lung adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
(22 reference statements)
1
20
0
Order By: Relevance
“…However, it has been reported that a Japanese cohort of 347 patients with stage IA lung adenocarcinoma had a low frequency (1.7%) of the micropapillary‐predominant pattern, which was similar to the finding in our cohort (1.4%) . Conversely, we have reported previously that the presence of solid and/or micropapillary components (≥ 1% of the entire tumour) predicted a worse prognosis in patients with acinar‐ and papillary‐predominant lung adenocarcinoma measuring ≤3 cm . Therefore, we focused upon the clinical significance of the presence of solid and/or micropapillary components (≥ 1% of the entire tumour) in patients with new TNM p‐stage IA lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, it has been reported that a Japanese cohort of 347 patients with stage IA lung adenocarcinoma had a low frequency (1.7%) of the micropapillary‐predominant pattern, which was similar to the finding in our cohort (1.4%) . Conversely, we have reported previously that the presence of solid and/or micropapillary components (≥ 1% of the entire tumour) predicted a worse prognosis in patients with acinar‐ and papillary‐predominant lung adenocarcinoma measuring ≤3 cm . Therefore, we focused upon the clinical significance of the presence of solid and/or micropapillary components (≥ 1% of the entire tumour) in patients with new TNM p‐stage IA lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 89%
“…8 Conversely, we have reported previously that the presence of solid and/or micropapillary components (≥ 1% of the entire tumour) predicted a worse prognosis in patients with acinar-and papillary-predominant lung adenocarcinoma measuring ≤3 cm. 11 Therefore, we focused upon the clinical significance of the presence of solid and/or micropapillary components (≥ 1% of the entire tumour) in patients with new TNM p-stage IA lung adenocarcinoma. The inclusion of both the new TNM classification and well-known established prognostic factors in our analysis strengthened the reliability of our results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations